A comparison of strength and EMG in elite weighters during six different directions of upper limb activities - Kao, M.; Yeh, L.; Tsai, S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. II, 2008)
Introduction The purpose of this study was to analyse and compare elite weight lifting participant`s upper limbs at six different positions (shoulder flexion, shoulder extension, shoulder abduction, horizontal adduction, elbow flexion and elbow extension their six muscles (anterior deltoid (Ant_Del), middle deltoid (Med_Del), posterior deltoid (Post_Del), pectoralis major (Pec), biceps (Bi) and triceps (Tri) on 100% MVC isometric contraction were investigated to understand the correlation between muscle strength and the weight lifting performance.